2016
DOI: 10.1007/s11127-016-0391-y
|View full text |Cite
|
Sign up to set email alerts
|

On the political economy of national tax revenue forecasts: evidence from OECD countries

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 64 publications
1
18
0
1
Order By: Relevance
“…In contrast, Boylan () finds biases in forecasts for an array of U.S. state budget variables from 1982 to 2005 and attributes them to both economic and political factors. This is confirmed by Jochimsen and Lehmann () for a sample of 18 OECD countries. They find that left‐wing and less fragmented governments produce more optimistic tax revenue forecasts; they do, however, not find any evidence for political budget cycles.…”
supporting
confidence: 74%
“…In contrast, Boylan () finds biases in forecasts for an array of U.S. state budget variables from 1982 to 2005 and attributes them to both economic and political factors. This is confirmed by Jochimsen and Lehmann () for a sample of 18 OECD countries. They find that left‐wing and less fragmented governments produce more optimistic tax revenue forecasts; they do, however, not find any evidence for political budget cycles.…”
supporting
confidence: 74%
“…In the budgetary planning process more positive economic forecasts lead to overestimated tax revenues, generating a potential spending leeway for the politicians. Higher tax revenue forecasts therefore either lead to higher expenditures by keeping the ex-ante deficit constant or to a reduction of the ex-ante deficit by keeping expenditures at its former level (see Jochimsen and Lehmann, 2017). In the context of our stylized model we assume that the government has an incentive − at time − to systematically deviate from the optimal unbiased forecast and to produce over-optimistic forecasts ( − > 0).…”
Section: Biased Forecasts: Political Economy Argumentsmentioning
confidence: 99%
“…Initially this result seems to be puzzling. But it becomes less so if we take a closer look at the fiscal forecasting literature (see Goeminne et al, 2008;Jochimsen and Lehmann, 2017), which gives three reasons for a higher degree of fractionalization leading to less optimistic or more pessimistic forecasts. First, the more parties are part of the parliament the higher is the representation of interest groups from the population.…”
Section: Political Motives Of the Deviationmentioning
confidence: 99%
See 1 more Smart Citation
“…Buettner and Kauder [3], also working with data from Germany, found that Federal tax revenue forecasts were typically unbiased but still influenced by government. Jochimsen and Lehmann [4] examined national tax revenue forecasts for a sample of 18 OECD countries. They find strong support for a politically partisan effect on national forecasts of tax revenues.…”
Section: Forecasting Uk Tax Revenuesmentioning
confidence: 99%